Language as an Instrument of Domination: A Bourdieusian Analysis of Power Relations in Danielle Steel’s Malice - Amalia, Eliza; Nur, Tadjuddin; Alawiyah, Siti Tuti (International Journal of English and Applied Linguistics (IJEAL), 2025)
This study investigated how language functioned as an instrument of domination in Danielle Steel’s Malice. The research applied a qualitative descriptive method to analyze eighteen utterances containing verbal aggression that represented symbolic power. Using Pierre Bourdieu’s theory of habitus, field, capital, and symbolic power, the study described how linguistic expressions constructed and legitimized social hierarchy within the domestic sphere. The analysis revealed that domination in the novel was expressed through subtle forms of symbolic violence rather than physical aggression. The findings showed three major patterns: first, moral coercion and emotional manipulation disguised as affection; second, legitimate language used by institutional voices to reinforce authority; and third, the internalization of power that produced silence and obedience. Through these findings, language was proven to operate as a social mechanism that transforms coercion into moral duty. The study concluded that symbolic power endures because it is accepted as care, gratitude, and love, revealing that domination persists most effectively when expressed through everyday language.